In-situ synthesis of 0D/1D CeO2/Zn0.4Cd0.6S S-scheme heterostructures for boosting photocatalytic remove of antibiotic and chromium. Issue 4 (15th February 2023) - Zhang, Min; Zhao, Xue; Dong, Yunyuan; Hu, Chenyao; Xiang, Xiaokang; Zeng, Xiantao; Jia, Junhao; Jin, Chen; Ding, Liang; Chen, Xiaobin
Abstract: The development of green and efficient photocatalytic materials for the treatment of medical and industrial wastewater has become a current research focus. In this work, the CeO2 /Zn0.4 Cd0.6 S heterojunction with a special 0D/1D morphology was synthesized by a soft chemistry method. The successful construction of the heterojunction was verified by the binding energy migration of XPS and TEM. The photocatalytic activities were determined by photoreduction of hexavalent chromium ions (Cr VI ) and photodegradation of tetracycline hydrochloride (TC). The experimental results showed that the loading of CeO2 significantly improves the photocatalytic performance of Zn0.4 Cd0.6 S, and the loading of 10 wt% CeO2 has the best photocatalytic activity and structural stability. The S-scheme electron transport mechanism was particularly investigated through active species trapping experiments. This work provides an effective idea for the design of highly stable metal sulfide photocatalysts. Graphical abstract: Image 1